Molecular mechanisms underlying haplotypespecific regulation of gene expression at the microtubule associated protein tau locus - Lai, MC (2016)
Genome wide association studies (GWAS) have identified the H1 microtubule associated protein tau (MAPT) haplotype single nucleotide polymorphisms as leading common risk variants for Parkinson's disease (PD), progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD). Gene expression studies have demonstrated haplotype-specific increases in expression of MAPT exon 3-containing transcripts from the protective H2 allele compared to the H1. The difference in alternative splicing between the haplotypes likely contributes risk or protection in the absence of protein coding variants. Here, we investigate the regulation of MAPT exon 3 alternative splicing by common, risk-associated, non-coding, haplotype-specific single nucleotide polymorphisms (SNPs) through a combination of in silico analysis of the MAPT locus, in vitro gene expression and biochemistry studies. Comparative sequence analysis of whole-locus genomic H1 and H2 MAPT (143 kb) vectors showed they capture over 86% of the MAPT sequence diversity. We generated and expressed haplotype-hybrid H1 and H2 MAPT vectors in a human neuroblastoma cell culture model and demonstrated that a functional SNP rs17651213 near the exon 3 5' splice site regulates exon 3 inclusion in a haplotype-specific manner. Using RNA-electrophoretic mobility shift assays (RNA-EMSA), we showed differential RNA-protein complex formation at the H1 and H2 sequence variants of SNP rs17651213. We further identified candidate trans-acting splicing factors interacting with functional SNP rs17651213 sequences by RNA-protein pull-down experiment and mass spectrometry. Finally, gene knockdown of candidate splice factors identified by mass spectrometry demonstrated a role for hnRNP F and hnRNP Q in the haplotype-specific regulation of exon 3 inclusion. In this study, we have dissected the MAPT locus to identify sequences regulating the allele-specific alternative splicing of exon 3 and provided mechanistic insights into how common non-coding H1/H2 MAPT haplotype-specific SNPs may contribute to the risk/protection of neurodegeneration at a complex genetic locus.